1999
DOI: 10.1007/bf02481519
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight distribution of regular asphalts from dynamic material functions

Abstract: A B S T R A C T R [ S U M EDynamic material functions are among the most sensitive tools for determining the molecular weight distribution ofrheologically complex systems. The phase angle of the complex modulus especially is sensitive to the molecular weight of the studied material; it can therefore be used as the input to the inverse problem of determining the molecular weight from this important dynamic material function. Molecular weight distributions of several regular asphalts are calculated using the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…In general, Figure 6 clearly shows the internal structural changes of modified asphalt binders. From Figure 6a, the phase angle inversion method gives similar number-average molecular weight of around 800 Da for base asphalt as reported in the literature using GPC test (14,15,32). This comparable result verifies the robustness of the inversion method.…”
Section: From Rheology To Molecular Weight Distributionsupporting
confidence: 81%
See 1 more Smart Citation
“…In general, Figure 6 clearly shows the internal structural changes of modified asphalt binders. From Figure 6a, the phase angle inversion method gives similar number-average molecular weight of around 800 Da for base asphalt as reported in the literature using GPC test (14,15,32). This comparable result verifies the robustness of the inversion method.…”
Section: From Rheology To Molecular Weight Distributionsupporting
confidence: 81%
“…It was found that the MWDs calculated from rheological data are in good agreement with the corresponding GPC data. In subsequent research, Zanzotto et al (14) found the phase angle to be more sensitive to molecular weight changes than the complex modulus. In addition, they noted that GPC is more sensitive to low molecular weights while the rheological inversion yields a higher resolution in a high molecular weight band.…”
Section: Relationship Between Rheology and Molecular Weight Distributionmentioning
confidence: 99%
“…Emails: andrea.themeli@yahoo.com; emmanuel.chailleux@ifsttar.fr It is well known that mechanical properties of materials depend on the molecular weights (MW) of their components and MWD (Ferry, 1980). For example, it has been shown that a clear correlation exists between the MW of polymers or bitumens and their rheological behaviour (Lesueur, 2009b;Tuminello, 1986;Tuminello & Mauroux, 1991;Wu, 1988;Zanzotto, Stastna, & Ho, 1999). Inverting this relationship would allow the calculation of the MWD from the measured mechanical property.…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between rheological properties of bitumen and its molecular weight distribution (MWD) is generally assumed in the literature (27)(28)(29)(30)(31). The basic assumption of the δ-method is that for a given frequency, the phase angle of the complex modulus is proportional to the fraction of relaxed molecules at this frequency.…”
Section: δ-Methods Applicationmentioning
confidence: 99%